2020
DOI: 10.3390/en13174517
|View full text |Cite
|
Sign up to set email alerts
|

Biorefinery of the Olive Tree—Production of Sugars from Enzymatic Hydrolysis of Olive Stone Pretreated by Alkaline Extrusion

Abstract: This work addresses for the first time the study of olive stone (OS) biomass pretreatment by reactive extrusion technology using NaOH as the chemical agent. It is considered as a first step in the biological conversion process of the carbohydrates contained in the material into bio-based products. OS is a sub-product of the olive oil extraction process that could be used in a context of a multi-feedstock and multi-product biorefinery encompassing all residues generated around the olive oil production sector. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
(58 reference statements)
2
3
1
Order By: Relevance
“…In contrast to the results obtained in this study, Domenech et al [ 38 ] reported no changes in cellulose content after subjecting olive stone to alkali extrusion, independently of pretreatment temperature or the concentration of soda. However, these authors observed a slight decrease in hemicellulose content of the collected WIS fraction after extrusion pretreatment.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the results obtained in this study, Domenech et al [ 38 ] reported no changes in cellulose content after subjecting olive stone to alkali extrusion, independently of pretreatment temperature or the concentration of soda. However, these authors observed a slight decrease in hemicellulose content of the collected WIS fraction after extrusion pretreatment.…”
Section: Resultscontrasting
confidence: 99%
“…However, such an increase can also be attributed to the solubilization of extracts, as commented previously for carbohydrate content. A similar trend was observed by Doménech et al [ 38 ], who reported an increase of lignin content in pretreated olive stone from 33.8% in the raw material to 39.0% and 41.9% after extrusion at 100 °C with 5 and 10 g NaOH/100 g of olive stone, respectively. An increase in lignin content from 17.8% to 26.4–27.3% was also observed by Negro and co-workers [ 31 ] after subjecting olive tree pruning biomass to alkaline extrusion with 5 and 10% g NaOH/g dry matter ratio and a barrel temperature of 70–110 °C.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Some examples of biorefineries based on OS that outline different valorization routes for the carbohydrates present in these biomasses were gathered in the review by Ruiz et al [9]. Moreover, different strategies have been proposed to access the hexoses and pentoses from OS, such as acid hydrolysis followed by detoxification [25] or alkaline extrusion [13].…”
Section: Structural Composition Of Olive By-productsmentioning
confidence: 99%
“…Their structural composition consists of up to 50% sugar in the form of cellulose and hemicellulose and 25%-27% lignin [10]. This also grants them a potential use as a raw material in a biorefinery, as the research in this field focuses on its fractionation in order to maximize sugars liberation for further bioconversion [13]; • EOP is the leftover biomass obtained after the oil extraction of olive pomace, making up a 20% of the total dry mass of the pomace, which in turn constitutes 70%-80% of the total weight of the olive itself [14]. Pomace can be reused for further olive oil extraction by means of a solvent extraction process and a refining process and has been reported to be a source of high-value-added compounds such as phenols and polyphenols, vitamins, fatty acids, and other relevant antioxidants [10].…”
mentioning
confidence: 99%